Experiences of women on the use of Implanon NXT in Gauteng province, South Africa: A qualitative study - Junior M. Ntimani; Moreoagae B. Randa (AOSIS, 2024)
Background: Maternal-related illnesses and pregnancy-related deaths could be averted using contraceptives, particularly long-acting methods because they improve overall access to family planning because of their benefits, such as fewer visits to the healthcare facility, higher effectiveness and value for money. The introduction of Implanon NXT in the South African health system raised great concern about the number of women who returned to healthcare facilities for its early removal within a few months of insertion. Aim: This article focussed on exploring the experiences of women regarding early removal of Implanon NXT insertion. Setting: The study was conducted in four selected clinics in Region E sub-district, city of Johannesburg. Methods: A qualitative exploratory approach was followed using semi-structured individual interviews to collect data. Data were analysed using the content analysis method. Results: The most cited reasons for its discontinuity were that women experienced unpleasant side effects such as amenorrhoea, excessive bleeding and headaches, whilst other women found it to be reliable and convenient. Conclusion: Contraceptive methods empower women to take control of their lives and to decide on the right time for them to have children. It is, therefore, important to equip women with relevant information about the contraceptive methods so that they can make informed decisions and choices. Contribution: The study calls for health promoters to periodically conduct information sessions with women as guided by the National Contraception Policy Guidelines to ensure up-to-date practice.